The Role of Social Media as a Learning Platform in the Covid-19 Pandemic - Iin Dwi Aristy Putri; Alim Surya Saruman; Ikram Lihu; Muhammad Samil Ilyas (Universitas Negeri Makassar, 2021)
Educators as human resources must be able to adapt to various advances in science and technology. As a professional, educators must be able to plan, implement, and assess the learning that has been done. By taking advantage of the opportunity to increase the intensity of the use of social media during the pandemic, educators must also be ready to learn to continue to increase their creativity and innovation in planning interesting learning. The purpose of the study was to determine the role of social media as a learning platform in the era of covid 19. The results showed that by utilizing social media, especially whatsapp as a supporter of the learning process, it was able to have a positive influence, especially during the current covid-19 pandemic. Both as teaching staff and students feel the use of WhatsApp social media itself, in exploring their abilities, especially in using the media in creating assignments and materials in learning.